The cost and benefit of targeting amyloid plaques to treat alzheimer's disease - Marisa E Franklin; Glen A Franklin (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2023)
Alzheimer's Ddisease (AD) is now the seventh leading cause of death in the United States. This incurable and fatal disease is becoming an increasingly concerning medical diagnosis. One feature of Alzheimer's disease is a build-up of the peptide amyloid-beta in the brain that progressively interferes with the patient's ability to retain memory and perform mental tasks. One of the newest strategies to combat AD is to target the excess amyloid-beta. Several new drugs have been in stages of clinical trials, with both Lecanemab and Aducanumab recently being deemed a scientific breakthrough by gaining Food and Drug Administration (FDA) approval. This review will address the various strategies scientists have taken to target amyloid-beta, discuss the cost versus benefit of the drugs, and attempt to place this information in context with this significant public health crisis.